Perbedaan Kejadian Hemolisis antara Lama Penyimpanan Komponen Darah Packed Red Cell (PRC) dengan Whole Blood (WB) di UTD PMI Surabaya - Lentera Afrida Kusumawardani; Reinaldi Angga Ardhana (Jurnal Medika Nusantara, 2025)
Packed Red Cell (PRC) is a commonly used blood component for transfusion, obtained through centrifugation or sedimentation of Whole Blood (WB), with most of the plasma removed. During in vitro storage, changes such as reduced red blood cell viability and hemolysis can occur. At UTD PMI Surabaya, hemolysis in PRC and WB was detected on the 20th day of storage, with 10% of blood production approaching hemolysis. This study aims to determine the differences in hemolysis events based on storage duration between PRC and WB. The research used a total sampling method with 60 combined samples of PRC and WB and was conducted at UTD PMI Surabaya. Statistical analysis using a paired samples t-test showed a significant value of p = 0.000 (p < 0.05), indicating a significant difference in hemolysis events between PRC and WB. The study concludes that there is a significant difference in hemolysis events based on storage duration between PRC and WB at UTD PMI Surabaya.